Three‐phase hollow fiber liquid‐phase microextraction based on a magnetofluid for the analysis of aristolochic acids in plasma by high‐performance liquid chromatography. Issue 13 (7th May 2014) - Song, Rui Juan; Pu, Feng Ping; Zhou, Jun; Sun, Jiang Bing; Zeng, Ping; Zhang, Qiong
<x xml:space="preserve">Abstract</x> A new and fast sample preparation technique based on three‐phase hollow fiber liquid‐phase microextraction with a magnetofluid was developed and successfully used to quantify the aristolochic acid I (AA‐I) and AA‐II in plasma after oral administration of Caulis akebiae extract. Analysis was accomplished by reversed‐phase high‐performance liquid chromatography with fluorescence detection. Parameters that affect the hollow fiber liquid‐phase microextraction processes, such as the solvent type, pH of donor and acceptor phases, content of magnetofluid, salt content, stirring speed, hollow fiber length, extraction temperature, and extraction time, were investigated and optimized. Under the optimized conditions, the preconcentration factors for AA‐I and AA‐II were >627. The calibration curve for two AAs was linear in the range of 0.1–10 ng/mL with the correlation coefficients >0.9997. The intraday and interday precision was <5.71% and the LODs were 11 pg/mL for AA‐I and 13 pg/mL for AA‐II (S/N = 3). The separation and determination of the two AAs in plasma after oral administration of C. akebiae extract were completed by the validated method.